Difficulty walking as the main manifestation of scurvy in children: two cases from a resource-limited setting - Angelina, Angelina; Aviana, Ruthie; Ardelia, Yolanda; Dewi, Arfianti Chandra; Sidauruk, Ratno Juniarto Marulitua (Indonesian Pediatric Society, 2025)
Scurvy is a disease caused by a prolonged deficiency of vitamin C. It was first reported in Egypt in 1500 before century (BC) and formally described by the writings of Hippocrates as “the mouth feels bad, the gums are detached from the teeth, blood runs from the nostrils, black-colored ulcerations frequently appear on the legs, some of these heal, others not, and the skin is thin.”1,2 Scurvy has become an uncommon disease nowadays, especially in developed countries. However, there have been sporadic case reports of scurvy in children. One of the largest cohorts of scurvy cases in children took place in Thailand in 2003, where 28 children diagnosed with scurvy manifested with a limp or inability to walk.3